2018
DOI: 10.1016/j.celrep.2018.03.067
|View full text |Cite
|
Sign up to set email alerts
|

FOXF1 Inhibits Pulmonary Fibrosis by Preventing CDH2-CDH11 Cadherin Switch in Myofibroblasts

Abstract: SUMMARYIdiopathic pulmonary fibrosis (IPF) is characterized by aberrant accumulation of collagen-secreting myofibroblasts. Development of effective therapies is limited due to incomplete understanding of molecular mechanisms regulating myofibroblast expansion. FOXF1 transcription factor is expressed in resident lung fibroblasts, but its role in lung fibrosis remains unknown due to the lack of genetic mouse models. Through comprehensive analysis of human IPF genomics data, lung biopsies, and transgenic mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…Vehicle control and RCM-1-treated tumor cells were incubated with EdU or bromodeoxyuridine (BrdU), and immunofluorescence staining for EdU, BrdU, PH3, and Ki67 was performed as previously described (31,32).…”
Section: -Ethynyl-2 0 -Deoxyuridine (Edu) and Bromodeoxyuridine Incomentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle control and RCM-1-treated tumor cells were incubated with EdU or bromodeoxyuridine (BrdU), and immunofluorescence staining for EdU, BrdU, PH3, and Ki67 was performed as previously described (31,32).…”
Section: -Ethynyl-2 0 -Deoxyuridine (Edu) and Bromodeoxyuridine Incomentioning
confidence: 99%
“…Lung tissue sections were stained using anti-FOXM-1, anti-Ki-67, anti-PH3 (Santa Cruz Biotechnology), and anti-cleaved caspase-3 (Abcam) antibodies, as described previously (33). Tumor cells growing on coverslips were treated with 20 mmol/L of RCM-1 for 24 hours, fixed, and stained with antibodies against FOXM1, FOXA1, b-catenin, Ki-67, and a-tubulin (Santa Cruz Biotechnology) as previously described (32).…”
Section: Ihc Immunofluorescence and Confocal Imagingmentioning
confidence: 99%
“…Previously, Belkhir et al reported that Foxf1 expression was induced by the antifibrotic mediator prostaglandin E2 and repressed by TGF-β in pulmonary fibroblasts [35]. The vital role of FOXF1 in the pathogenesis of IPF was later highlighted by the observation that loss of Foxf1 increased migration of pulmonary fibroblasts via facilitating CDH2-CDH11 cadherin switch and thus aggravated bleomycin-induced pulmonary fibrosis in mice [22]. Consistent with these literatures, our results showed the significant downregulation of Foxf1 in both fibrotic mice lungs and primary mouse pulmonary fibroblasts incubated with TGF-β and further demonstrated that rKL was sufficient to reverse the reduction of Foxf1, which subsequently attenuated TGF-β-induced migration of pulmonary fibroblasts through preventing CDH2-CDH11 cadherin switch.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased protein levels of Foxf1 were also confirmed by western blot ( Figure 6C). Since Foxf1 has been reported to inhibit pulmonary fibrosis by preventing CDH2 to CDH11 cadherin switch in myofibroblasts during pulmonary fibrosis [22], we proposed that Kl be very likely to repress the TGF-β-induced migration of pulmonary fibroblasts via enhancing the expression of Foxf1. As hypothesized, rKL supplementation restored Foxf1 mRNA and protein levels in both PCLSs treated with FC ( Figure 6D and 6E) and pulmonary fibroblasts incubated with TGF-β ( Figure 6F and 6G).…”
Section: Foxf1 Deletion Reverses the Inhibitory Effect Of Kl On Pulmomentioning
confidence: 96%
See 1 more Smart Citation